A parametric study of nose landing gear noise in a large-scale aeroacoustic wind tunnel. (December 2022) - Zhao, Kun; Zhang, Rongping; Kopiev, Victor; Belyaev, Ivan; Okolo, Patrick N.
Abstract: The nose landing gear (NLG) of an aircraft considerably contributes to the undercarriage noise. In this paper, a large-scale testing program was conducted within the FL-17 5.5 m × 4 m aeroacoustic wind tunnel in CARDC to characterize the effects from various parameters on the acoustic performance of a generic NLG model. Those investigated parameters include incoming flow velocity, wheel size, height, angle of attack and yaw angles. The test was majorly comprised of noise source localization and free-field sound pressure level spectra analysis. Two categories of tonal noise were distinguished depending on variation between frequency and incoming flow speed. Effects of the sideline directivity were analyzed, and it was found that the side distribution of OASPL shows a saddle-like trend with the flow/flight direction and the tonal noise changes significantly with directivity angle. Regarding spectral scaling, U ∞ 7 was found to be more appropriate for a large-scale NLG model, while for a compact small-scale NLG model, the traditional U ∞ 6 is still recommended. As to transitional size, a combination of U ∞ 7 and U ∞ 6 showed to be more suitable for scaling within the high and low frequency ranges respectively. Contributions of different elements to NLG noise to different noise sources were discussed, which were found not to be dependent on their relative sizes. Analysis of the wheel diameter showed it does not cause obvious changes to the overall spectra trend but can induce variation of the amplitude and frequency tones. When the wheel is sufficiently small, the upper head of the sliding piston can be directly exposed to the incoming flow and thus generate sharp tonal noise. In terms of NLG height, the main effects on the acoustic performance was found to be associated not with the change in the height itself, but rather with the accompanying changes from other elements. Finally, the effects of angle of attack ( α ) and yaw angle ( β ) were analyzed with results showing that the angle of attack could potentially lead to substantial changes in the acoustic performance, while the yaw angle within 0 ° - 8 ° has minimal effects.